2022
DOI: 10.23919/ien.2022.0050
|View full text |Cite
|
Sign up to set email alerts
|

China's 10-year progress in DC gas-insulated equipment: From basic research to industry perspective

Abstract: The construction of the future energy structure of China under the 2050 carbon-neutral vision requires compact direct current (DC) gas-insulation equipment as important nodes and solutions to support electric power transmission and distribution of long-distance and large-capacity. This paper reviews China's 10-year progress in DC gas-insulated equipment. Important progresses in basic research and industry perspective are presented, with related scientific issues and technical bottlenecks being discussed. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 157 publications
(188 reference statements)
0
23
0
Order By: Relevance
“…By combining Equations (3)(4)(5), the surface charge dynamic model has been established recently by considering conduction processes in gas, gas-solid, and solid [140,155]. Zhang et al calculated the surface charge distribution of PTFE (Figure 5cii, right figure) and found that the surface charge behaves in accordance with the experimental results (Figure 5c-ii, left figure) [140].…”
Section: Gas Ionisation Versus Surface Conduction Versus Bulk Conductionmentioning
confidence: 90%
See 2 more Smart Citations
“…By combining Equations (3)(4)(5), the surface charge dynamic model has been established recently by considering conduction processes in gas, gas-solid, and solid [140,155]. Zhang et al calculated the surface charge distribution of PTFE (Figure 5cii, right figure) and found that the surface charge behaves in accordance with the experimental results (Figure 5c-ii, left figure) [140].…”
Section: Gas Ionisation Versus Surface Conduction Versus Bulk Conductionmentioning
confidence: 90%
“…Collision ionisation in gas phase Plasma expansion Computable (4). Surface states (Surface morphology [79][80][81][82], roughness [83][84][85][86][87], charging [88][89][90][91][92], surface gas [17,24,93,94] etc.…”
Section: Gas-solid Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface coating has been proved to as a novel modification method to improve the insulation performance of DC GIL/ GIS epoxy insulators [20][21][22]. Especially, the dielectric composite with nonlinear conductivity is considered as flexible smart surface coating for future DC-GIL/GIS insulators [23,24]. Li et al developed a field-graded coating of CaCu 3 Ti 4 O 12 (CCTO) using magnetron sputtering and observed that the 90min sputtered spacer significantly improved the surface electric field distribution and flashover voltages under various DC testing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…From the beginning of the 21st century, new energy power access grids have become the primary measures for energy consumption as well as environmental pollution which resulted from the high-speed development of society. [1][2][3][4] To solve profound changes in a power grid structure and operation characteristics brought about by the progress of large-scale new energy access and transmission technology, [5][6][7] and realize the transformation to a new power system characterized by safety and efficiency, clean and low-carbon, flexible and intelligent integration, interconnection technologies such as the digital twin and Internet of Things have been widely applied. 8,9 The construction and operation of the new power system require monitoring and analysis of the running state of each node in the power grid, so as to realize the efficient coordination and coordination control of various power sources, power grids, loads, and energy storage in the new power system.…”
Section: Introductionmentioning
confidence: 99%